Frequency analysis of EEG signal generated from dyslexic children - Che Wan Fadzal, C. W. N. F.; Mansor, W.; Lee, K. Y.; Mohamad, S.; Amirin, S. (2012 IEEE Symposium on Computer Applications and Industrial Electronics, 2012)
Dyslexia is a neurological disorder which needs to be detected at an early stage to know their specific needs and to help them cope with the problem. One of the ways to detect dyslexia is by using Electroencephalogram (EEG). In this study, the EEG signals recorded from dyslexic's children while performing writing activities were analyzed. The EEG signals were recorded from 4 channels; C3, C4, P3 and P4 and filtered using band pass filter with frequency range 8 Hz to 30 Hz. The signal was analyzed using Fast Fourier Transform. Analysis of EEG signals showed that the range of frequency for dyslexic children during writing is 22-28 Hz which is considered high and indicates that they are trying hard to write a correct word.